Assessing writing - Weigle, Sara Cushing (Cambridge University Press, 2002)
"Writing is a key skill in second language learning and all teachers need to evaluate their students' writing abilities. The issues surrounding the assessment of second language learners' writing abilities are becoming more and more relevant in the age of global communication and this is the first book to look at the assessment of this core skill in both academic and non-academic settings in a clear and accessible manner. It looks at the theory behind the practice and provides practical guidance on developing both small and large-scale writing tests. If you need to evaluate your students' writing then this book is essential reading."--Jacket.